The Disposition Effect in Mutual Funds: Evidence from Iran - Ali Ebrahim Nejad (University of Tehran, 2021)
Objective: The disposition effect refers to the tendency of selling stocks that have appreciated at price and holding stocks whose price is lower than the purchase price. Although an extensive literature has examined and confirmed the existence of the disposition effect among individual investors, there is no consensus in the literature as to whether institutional investors are also subject to similar behavioral biases or not. We test for the presence of the disposition effect among a sample of Iranian mutual funds. Methods: We measure the disposition effect both at the aggregate and fund level, using hand-collected quarterly transactions data for a sample of Iranian mutual funds from 2010 to 2017. Our data has two unique features compared to similar studies; first, we know the exact buying price of stocks held in mutual funds' portfolios, whereas most studies need to estimate the buying price by making assumptions about purchase timing and using the prevailing market prices as a proxy. Second, unlike most studied markets, there are no capital gains taxes on the Tehran Stock Exchange and tax-motivated trading does not affect our findings. Results: We find that Iranian mutual funds tend to sell winning stocks more quickly than losing stocks. To be specific, the probability of selling a winning stock is approximately 1.46 times the probability that a losing stock be sold. Excluding taxes and commissions in calculating the realized profit on the sold stocks, the ratio grows to 1.51. The measured disposition effect is not driven by the effect of tax-motivated selling, since there are no capital gains taxes on the Tehran Stock Exchange. The documented disposition effect cannot be explained by funds’ internal portfolio rebalancing regulations nor by the potentially higher trading cost of selling low-priced stocks. The disposition effect exhibits a mild downward trend line throughout the sample period; however, the downward trend is not statistically significant. Partitioning the data based on the fund's portfolio value shows that both more skilled and less skilled fund managers – as proxied by fund size - are prone to the disposition effect. Conclusion: Our study finds strong support for the disposition effect among mutual funds. Our results are relevant for both mutual fund managers and policy-makers.